2014
DOI: 10.4236/ojas.2014.45035
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Performance and Mortality Rate in Local and Dorper &#215 Local Crossbred Sheep Following Controlled Breeding in Ethiopia

Abstract: The reproductive and lamb mortality data (n = 187) of the Local and crosses of Dorper × Local ewes following natural controlled breeding in Ethiopia were analysed. Data were collected during 2009-2011 at Sirinka breeding, evaluation and distribution site, eastern Amhara region of Ethiopia. Breed, lamb sex, birth season, birth year, birth type and ewes' parity were considered as fixed effects. Data analyses were performed using general linear model procedures. Breed was a significant source of variation: the lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 7 publications
3
15
1
Order By: Relevance
“…The current study observed that crossbreeding with Dorper sheep improved the growth rate of the local sheep by 89 and 78% at 6 and 9 month age, respectively (Figure 2). This result of the current finding is in line to the previous of Lakew et al (2014) who found that the crossbred ewes were found weighed more than the local sheep ewes at adult age (32.7 ± 0.63 vs. 22.8 ± 0.43 kg).…”
Section: Improvement On the Meat Production Performance Of The Local supporting
confidence: 93%
See 1 more Smart Citation
“…The current study observed that crossbreeding with Dorper sheep improved the growth rate of the local sheep by 89 and 78% at 6 and 9 month age, respectively (Figure 2). This result of the current finding is in line to the previous of Lakew et al (2014) who found that the crossbred ewes were found weighed more than the local sheep ewes at adult age (32.7 ± 0.63 vs. 22.8 ± 0.43 kg).…”
Section: Improvement On the Meat Production Performance Of The Local supporting
confidence: 93%
“…The body weight performances of the Dorper crossbred have got premium result in improving the local sheep worldwide (Lakew et al, 2014). The current suggested that Dorper sheep is an appropriate technology for producing crossbred lambs with better growth rates under smallholder farmers (Figure 3).…”
Section: Improvement On the Meat Production Performance Of The Local mentioning
confidence: 99%
“…The effect of year of birth and dam's weight at lambing were statistically significant on AFL, WL and GFW. Lakew et al (2014) also reported significant effect of year of birth on AFL and WL. Mir et al (2000) reported significant effect of year of birth on greasy fleece weight in Corriedale sheep.…”
Section: Resultsmentioning
confidence: 82%
“…However, the estimated birth weight of Dorper lambs under intensive condition was 3.8±0.8 kg (Mellado et al, 2016) and yearling weight reached an average weight of 55.0 kg at 18 months of age . In other cases Lakew et al, (2014) at Sirinka Agricultural Research Center found that the local sheep and their Dorper crosses mean birth weight and weight at weaning was 2.36±0.05 kg, 3.24±0.04 kg; 8.53±0.14 and 14.95±0.21kg, respectively. On station representative's of productive performance of indigenous and their cross with Dorper sheep are summarized in Table 3.…”
Section: On Station Performancementioning
confidence: 88%
“…Similar to this, heavier birth weight of pure Dorper (3.5 kg) as compared to crossed (3kg) was reported by . Lakew et al, (2014) mentioned that weaning, six months and yearling weights of 50% Dorper crossbreds were much higher with values of 14.95, 20.43 and 31.37 kg, respectively; as compared to the corresponding values for local breed in North Wollo lowland areas of Ethiopia with values of 8.53, 11.92 and 22.38 kg, respectively. In contrast, a study on response to feeding trial (Tilahun et al, 2014) identified that initial weight for local, 25% Dorper and 50 % Dorper at about 7 months were 14.8, 20.3 and 17.9, respectively; Final weight after 90 days were 22.8, 32.2 and 29.3 kg, respectively.…”
Section: On Station Performancementioning
confidence: 89%